Dynamics of natural discharge of the hydrothermal system and geyser eruption regime in the Valley of Geysers, Kamchatka - Kiryukhin A.V.; Polyakov A.Y.; Zhuravlev N.B.; Tsuchiya N.; Rychkova T.V.; Usacheva O.O.; Dubrovskaya I.K. (My University, 2021)
The total deep component natural mass discharge Qd (defined in terms of chloride mass discharge Qcl) of the Valley of Geysers, on an average ranges from 280 kg/s from 1961 to 1984, to 230 kg/s after 2015. Post 2012, discharge measurements reveal a seasonal variation: the discharge increases (340–370 kg/s) during the winterfrozen period, and decreases during the summer flooding period (≈100 kg/s). Long term annually averaged Qd is 274 kg/s, Qcl is 0.247 kg/s and heat flow is 265 MW. In the course of using high-frequency (min???? 1) observations specific conductance measurements from 2017 to 2020, the total natural discharge was found to be cycling due to the internal cycling of geysers. It was mostly sensitive to the Bolshoy and Velikan geysers with averaged intervals between eruptions of 60 min and 70 min, respectively. The tracer chloride method estimates the volume of hot water erupted from geysers. This method yielded the following estimates: 5–34 m3 of hot water cyclically erupted from the Bolshoy geyser; 0.5–4.5 m3 erupted from the Velikan geyser between 2018 and 2020, and 24–144 m3 erupted before the 2014 mud-flow disaster; and 289–330 m3 erupted from the Grot geyser between May–June 2012. The seasonal features of natural discharge mentioned above may be explained in terms of coldwater infiltration into a two-phase geyser geothermal reservoir, especially if gas-phase condensation induces vacuum conditions, which may further reduce some thermal discharge features.
Keywords: 38.61.03 Методы гидрогеологических исследований; 38.61.05 Моделирование гидрогеологических процессов; 38.61.15 Динамика и режим подземных вод; 38.61.17 Гидрогеохимия; 38.61.19 Минеральные, термальные воды и рассолы; Большой; Грот; _Долина гейзеров; _ Материалы общего характера, методы исследования; Великан